2013
DOI: 10.1089/acm.2012.0296
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Xilei-san, a Chinese Herbal Medicine, and Dexamethasone in Mild/Moderate Ulcerative Proctitis: A Double-Blind Randomized Clinical Trial

Abstract: Xilei-san enemas are comparable to dexamethasone enemas in this study. This medicine is safe, well accepted, and may be an alternative drug in the treatment of mild-to-moderate active UP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…After 6 months, the rate of recurrence was lower in the group of Xilei-San (Xilei-San 18.2% vs. placebo 83.3%, p < 0.001) [25] . In another randomized, double-blinded study that compared Xilei-San with dexamethasone enemas, a similarly significant clinical, histological and endoscopic response compared with the baseline in the 2 groups was achieved [26] . Importantly, no significant adverse side effects were observed in either study [25,26] .…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…After 6 months, the rate of recurrence was lower in the group of Xilei-San (Xilei-San 18.2% vs. placebo 83.3%, p < 0.001) [25] . In another randomized, double-blinded study that compared Xilei-San with dexamethasone enemas, a similarly significant clinical, histological and endoscopic response compared with the baseline in the 2 groups was achieved [26] . Importantly, no significant adverse side effects were observed in either study [25,26] .…”
Section: Discussionmentioning
confidence: 84%
“…In another randomized, double-blinded study that compared Xilei-San with dexamethasone enemas, a similarly significant clinical, histological and endoscopic response compared with the baseline in the 2 groups was achieved [26] . Importantly, no significant adverse side effects were observed in either study [25,26] . In the dextran sulfate sodium-induced colitis rat model, topical treatment with Xilei-San attenuates colitis by degrading proinflammatory mediators and promoting mucosal repair [29] .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Some examples are discussed here. In double-blind, randomised studies, Xilei-san (a traditional Chinese herbal medicine) suppositories were shown to be superior to placebo [41] and comparable to dexamethasone enemas [42] in proctitis. Curcumin is the active ingredient of turmeric and has been shown to have anti-inflammatory properties in experimental models of colitis.…”
Section: Proctitismentioning
confidence: 99%
“…In China, XLS is traditionally used in disorders that feature erosion or ulceration of mucosa or skin, including oral ulcer, esophagitis, erosive gastritis, peptic ulcer, chronic cervicitis, and UC [6–12]. Although a few studies have investigated the mechanism of action of XLS in an animal model [11], the exact pharmacological steps of XLS in UC have never been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%